Funcionarios de Oficina de Recursos Humanos. (UNED, 2024)
Aparecen de pie arriba Ana Lucía Chaves Madrigal, Marvin Arce Jiménez, Ana Lorena Fallas Rivera, a la derecha Eduardo Castillo Arguedas, Ana Lorena Carvajal Pérez, Adela Saborío Álvarez, Mario Molina Valverde junto a otras tres personas